Micronutrient Intakes of British Adults Across Mid-Life: A Secondary Analysis of the UK National Diet and Nutrition Survey - Derbyshire, Emma (Frontiers in Nutrition, 2018)
Background: There is a tendency to report micronutrients intakes collectively for adults, with broad age ranges being used. This means that certain sub-population groups such as young adults are often overlooked. The objective of the present article was to derive and evaluate micronutrient intakes across UK adults in their twenties, thirties, forties and fifties. Methods: A secondary analysis of the UK National Diet and Nutrition Survey (years 1–6) was undertaken. Data from n = 3,238 adults was analyzed and micronutrient intakes from food sources (excluding supplements) derived as a percentage of the Reference Nutrient Intake (RNI) and percentage below the Lower Reference Nutrient Intake (LRNI) for males and females aged 20–29, 30–39, 40–49, and 50–59 years. Mean intakes were used in instances where this data was unavailable (for vitamins D and E). Results: Sizeable gaps were found for magnesium with 19% of young people in their twenties having intakes below the LRNI. Amongst UK females intakes of 9 micronutrients (riboflavin, vitamin B6, B12, folic acid, calcium, iron, magnesium, potassium, and iodine) were significantly lower than males aged 20–59 years (p < 0.001) expressed as a percentage of the RNI. Young adults in their twenties had significantly lower (p < 0.05) intakes of 8 micronutrients (vitamin A, riboflavin, folic acid, calcium, magnesium, potassium, iodine, and copper) expressed as a percentage of the RNI compared with adults in their thirties, forties and fifties. There were also considerable gaps in dietary selenium intakes with 50.3% females and 25.8% males having total intakes beneath the LRNI. A quarter of women had iron (25.3%) and potassium (24.3%) intakes below the LRNI. Conclusions: UK females and younger adults appear to be particularly vulnerable to micronutrient shortfalls from food sources alone. Clearly, improvements in dietary quality are needed across mid-life. Alongside this, fortification and supplementation strategies may be considered to help adults achieve dietary targets at this life-stage when they should be at their nutritional prime.